Phenotypic and genetic introgression across a moving woodpecker hybrid zone. Issue 7 (29th April 2019) - Billerman, Shawn M.; Cicero, Carla; Bowie, Rauri C. K.; Carling, Matthew D.
Abstract: In hybrid zones in which two divergent taxa come into secondary contact and interbreed, selection can maintain phenotypic diversity despite widespread genetic introgression. Red‐breasted ( Sphyrapicus ruber ) and red‐naped ( S. nuchalis ) sapsuckers meet and hybridize along a narrow contact zone that stretches from northern California to southern British Columbia. We found strong evidence for changes in the structure of this hybrid zone across time, with significant temporal shifts in allele frequencies and in the proportions of parental phenotypes across the landscape. In addition to these shifts, we found that differences in plumage predict genetic differences ( R 2  = 0.80), suggesting that plumage is a useful proxy for assessing ancestry. We also found a significant bimodal distribution of hybrids across the contact zone, suggesting that premating barriers may be driving reproductive isolation, perhaps as a result of assortative mating based on plumage differences. However, despite evidence of selection and strong patterns of population structure between parental samples, we found only weak patterns of genetic divergence. Using museum specimens and genomic data, this study of sapsuckers provides insight into the ways in which phenotypic and genetic structure have changed over a 40‐year period, as well as insight into the mechanisms that may contribute to the maintenance of the hybrid zone over time.